Penegakan Hukum Pidana dan Kearifan Lokal (Studi tentang Permainan Rolet pada Pagelaran Hiburan Rakyat di Kecamatan Juwana) - Murtadho, Ricky Alan; Kuswardani, K (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Technology that causes negative and positive effects that appear on humans, such as gambling that occurs with the progress of the times, gambling is an activity that is prohibited by religion and the state because it has an unfavorable influence on human activities, Gambling is a very large phenomenon. found in populated areas. Along with the development of the times, gambling can be carried out in various ways and in various forms. Gambling is universally seen as a crime. The crime of gambling or participating in and carrying out gambling acts was originally prohibited in the criminal provisions of Article 542 of the Criminal Code but stems from the provisions stipulated in Article 2 paragraph (4) of Law No. 7 of 1974 concerning the regulation of gambling, the name has been changed to a criminal requirement as regulated in Article 303bis of the Criminal Code.